2009
DOI: 10.3858/emm.2009.41.1.005
|View full text |Cite
|
Sign up to set email alerts
|

Association of TBX21 polymorphisms in a Korean population with rheumatoid arthritis

Abstract: TBX21 (T-bet) is a member of the T-box family of tran-scriptional factors that contain a conserved DNA binding domain. TBX21 is a critical regulator of the commitment to the Th1 lineage and IFN-γ production. Th1 and Th2 cells cross-regulate the differentiation of each other, and in this way TBX21 could be an attractive candidate gene for treating autoimmune disease such as rheumatoid arthritis (RA). In present study, we analyzed the genotypic frequencies of six polymorphisms of the TBX21 gene between the 367 R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
1
23
0
1
Order By: Relevance
“…This disease is arisen by the complex interaction between multiple genetic factors and environmental factors [8]. We previously suggested that the exon 4 variations of the Tim-1 gene [4], the eotaxin-3 polymorphisms [5] and the TBX21 polymorphism [6] are associated with RA susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…This disease is arisen by the complex interaction between multiple genetic factors and environmental factors [8]. We previously suggested that the exon 4 variations of the Tim-1 gene [4], the eotaxin-3 polymorphisms [5] and the TBX21 polymorphism [6] are associated with RA susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…1). Previously, several statistical analyses showed a positive association between T-1993C SNP or T-1514 C SNP (You et al 2010;Chae et al 2009) and autoimmune diseases. These observations indicate that both SNPs are involved in autoimmune diseases by affecting promoter activity.…”
Section: Frequencies Of −1993 and −1514 Snps In The Chinese Populationmentioning
confidence: 98%
“…For example, the associations between SNP haplotypes at −1514 and −1993 and SLE (You et al 2010), between T-1993C polymorphism and autoimmune hepatitis , and between T-1514C polymorphism and RA have been reported (Chae et al 2009). We previously analyzed the effect of a T-1993C polymorphism on the function of the TBX21 gene and found that the occurrence of an additional Yin Yang 1 (YY1) motif in the −1993C allele resulted in higher affinity to YY1, which subsequently caused lower transactivation of the promoter (Li et al 2011).…”
Section: Introductionmentioning
confidence: 96%
“…We previously suggested that the exon 4 variations of the Tim-1 gene [3], the eotaxin-3 polymorphisms [5], and TBX21 polymorphisms [4] are associated with RA susceptibility.…”
Section: Discussionmentioning
confidence: 99%